Business, Owner, and Regional Characteristics in Latino-owned Business Growth: An Empirical Analysis Using Confidential Census Microdata. (May 2020) - Carpenter, Craig Wesley; Loveridge, Scott
This article uses over 100, 000 observations from limited-access and nationally representative US Census Bureau microdata sets to test determinants of employment growth among Latino-owned businesses (LOBs) in the Unites States. We draw variables from prior studies on determinants business growth in the general population and uniquely apply them to LOB using the robust data. Specifically, we examine the impact of numerous business owner, business, and regional characteristics on employment growth. We include industry and state-level fixed effects and test the robustness of results to various employment growth timespans. Some findings include (1) Latina-owned businesses grow faster than LOB, (2) formal education has a positive effect on employment growth and this effect is larger with education level and time, (3) Puerto Rican-owned businesses grow 2 percent slower than Mexican-owned establishments, (4) having multiple establishments reduces employment growth, (5) relying on personal savings for start-up capital impedes growth, and (6) nonmetro adjacency has a significant and negative effect, while population density does not. Our findings show that LOB may grow differently than other businesses and help advance the understanding of factors related to success of LOB. Implementing straightforward and low-cost policies aimed at better support for LOB could help bolster regional growth.